2008
DOI: 10.1093/mp/ssm002
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced and Light-Independent Cryptochrome Photoreceptor Activation

Abstract: The cryptochrome photoreceptors of higher plants are dimeric proteins. Their N-terminal photosensory domain mediates dimerization, and the unique C-terminal extension (CCT) mediates signaling. We made use of the human FK506-binding protein (FKBP) that binds with high affinity to rapamycin or rapamycin analogs (rapalogs). The FKBP-rapamycin complex is recognized by another protein, FRB, thus allowing rapamycin-induced dimerization of two target proteins. Here we demonstrate by bioluminescence resonance energy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 65 publications
(90 reference statements)
0
51
0
1
Order By: Relevance
“…Both crys undergo B light-dependent phosphorylation, and the phosphorylation of the crys is closely correlated with their functions [47][48][49]. Homodimerization is required for the phosphorylation and physiological activity of the crys [50][51][52]. Recently, it was found that cry2 forms a homodimer in response to B light [53].…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 99%
“…Both crys undergo B light-dependent phosphorylation, and the phosphorylation of the crys is closely correlated with their functions [47][48][49]. Homodimerization is required for the phosphorylation and physiological activity of the crys [50][51][52]. Recently, it was found that cry2 forms a homodimer in response to B light [53].…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 99%
“…It is not clear as to how exactly CRY2-GFP could affect phosphorylation of the endogenous CRY2. However, given that cryptochromes form homodimers via the PHR domain (Sang et al, 2005;Rosenfeldt et al, 2007;Yu et al, 2007a), it is conceivable that phosphorylated CRY2-GFP might interact with the endogenous CRY2 to enable phosphorylation of the latter in the dark. Moreover, it is unclear as to whether or not CRY2-GFP itself might act as a kinase.…”
Section: Cry2-gfp Is Constitutively Phosphorylatedmentioning
confidence: 99%
“…The coding sequence of At-PHR1 was introduced into the NcoI site of pAVA393 (von Arnim et al 1998) 5Ј and in frame with the coding region of the GFP4/ GFP5 hybrid and 3Ј of the tandem CaMV 35S promoter. Protoplasts of an Arabidopsis Landsberg erecta mesophyll cell culture were transformed with the resulting construct pAVA393 At-PHR1::GFP as described by (Rosenfeldt et al 2008). The cellular localisation of the fusion protein was studied 16 h after transfection with a confocal microscope (Leica, Wetzlar, Germany) consisting of a DMRE stand equipped with an PL APO 63x/1.32-0.60 oil objective, a 65 nW Ar Laser and a TCS SP2 confocal scanner.…”
Section: Localisation Studiesmentioning
confidence: 99%